Les TIC et la surveillance des zones maritimes sensibles. Penser globalement, agir localement - Mélanie Fournier (Netcom)
What can have in common the geopolitics of the information, the geopolitics of the illicit and the maritime surveillance? Flows, territories and powers. The maritime areas are spaces of interactions, reduced to the harbor scale or widened when we talk about open sea. They link flows, commercial, civil and military information networks, as well as illegal networks. Even if in recent decades information systems have modified the geographical space and allowed the acceleration of decision making, the role of the information in a conflict is not new (alert, deciphering, jamming, damaging the enemy’s infrastructures, destabilization etc.). Nevertheless from a technical point of view the industrialists began the trend of the integrated systems. The crisis management and the real time maritime situational awareness are not any more divided up but not treated within a more global monitoring system with the aim of preventing and fighting against the risks and threats which transcend spaces. After introducing these major evolutions, this article will present the lessons of two case studies made by the author in the Caribbean area and the Mediterranean Sea.